The Role of Transformational Leadership, High-Performance Work Systems, and Psychological Capital in Work Engagement - Marsono Marsono; Dewi Puspaningtyas Faeni; H M Kemalsyah (Goodwood Publishing, 2026)
Purpose: This study examines the direct and indirect effects of Transformational Leadership (TL), High-Performance Work Systems (HPWS), and Psychological Capital (PsyCap) on Job Involvement (JI), with Work Engagement (WE) as the mediating mechanism. Research Methodology: This study used a quantitative method and survey design. All 300 active personnel of the 461st Pasgat Battalion of the Indonesian Air Force who met the minimum service requirements were included as respondents. Data were collected using a structured questionnaire and analyzed using SEM-PLS with bootstrapping. Results: TL, HPWS, and PsyCap significantly and positively influenced WE. Work Engagement (WE) also had a significant positive effect on JI. TL, HPWS, and PsyCap had significant direct effects on JI. The indirect effect results show that WE partially mediate the relationships between TL, HPWS, PsyCap, and JI, indicating that stronger leadership, better HR systems, and stronger psychological resources improve job involvement more effectively when they first increase engagement. Conclusions: Job involvement in the studied military unit is strengthened directly by leadership, high-performance work systems, and psychological capital, and indirectly through work engagement. Therefore, WE function as a key explanatory mechanism in the model. Limitations: The study is limited to one military unit, uses self-reported cross-sectional data, and does not include other contextual predictors such as job demands, leadership climate, or perceived organizational support. Contributions: This study reinforces the importance of integrating TL, HPWS, and PsyCap development to improve WE and JI in military settings. It also encourages future studies to adopt mixed-method approaches.